Application of IgH EtherCAT Master for Ultra-Precision Motion Control of Precision Axes - Zhihang Pan; Xuesen Zhao; Tianji Xing; Tao Sun (Micromachines)
The EtherCAT fieldbus system is widely applied in different types of computerized numerical control (CNC) machine tools due to its outstanding communication performance. In the field of ultra-precision CNC, some machine tools employ controllers that integrate EtherCAT master functionality to achieve real-time communication with other devices; however, the open-source IgH EtherCAT master has rarely been applied to the CNC systems of ultra-precision machine tools. The feasibility of using the IgH EtherCAT master to meet the communication performance requirements of ultra-precision machine tools remains uncertain; therefore, it is necessary to validate the control effect on precision axes under the application of the IgH EtherCAT master. In this work, EtherCAT applications were developed on a personal computer (PC) to alter it to a bus-type controller with the IgH EtherCAT master function. To provide the EtherCAT master with real-time and accurate motion data of the axes, an interpolation algorithm tailored for control experiments was designed, and a G-code data processing method was proposed. Moreover, precision aerostatic linear axes and servo drivers were chosen as EtherCAT slaves for single-axis motion and dual-axis linkage control experiments. The experimental results showed that the motion controller based on IgH can effectively control the precision axes to execute ultra-precision linear and circular interpolation motion.